Effect of probiotics in experimental otitis media with effusion. (May 2020) - Kaytez, Selda Kargin; Ocal, Ramazan; Yumusak, Nihat; Celi̇k, Hatiçe; Arslan, Necmi; Ibas, Mustafa
Abstract: Objectives: The article's aim was to investigate the effects of probiotics in the experimental otitis media with effusion. Materials and methods: Twenty-four male Wistar albino rats were used. They were divided into four groups. Experimental otitis media with effusion was created by intratympanic histamine injection. The effusion was confirmed by otomicroscopic examination 24 h after injection. Group 1; did not receive any treatment, group 2; received probiotics for 7 days after the detection of effusion, group 3; received probiotics for 7 days prior to injection of histamine, group 4; received probiotics for 7 days before injection of histamine and 7 days after detection of effusion. After detection of effusion, animals were sacrificed. Otomicroscopic evaluation was done to determine the effusion. In histopathological examination neutrophil leukocyte counts were determined in 25 areas of the sub-mucosa of the temporal bulla. Results: The otomicroscopic ear effusions' healing rate in group 1 was 10%, in group 2 was 25%, in group 3 was 50%, and in group 4 was 100% (p < 0, 013). The mean counts of submucosal neutrophil leukocyte from 25 areas of the temporal bulla of group 1 was 86, 8 ± 24, group 2 was 66, 5 ± 21, group 3 was 66, 2 ± 16, and group 4 was 26, 3 ± 6, 5 (p < 0, 001). Conclusion: Probiotics have a curative effect on the prevention and treatment of otitis media with effusion. This result may be related to their anti-inflammatory effects. Therefore, probiotics can be widely used in the age group at risk for otitis media with effusion as a complementary therapy by dietary supplements. Level of evidence: NA.